Applying the Key Biodiversity Area Standard to Important Sites for Sharks - Charlotte Boyd; Ryan Charles; Emiliano García‐Rodríguez; Adriana Gonzalez‐Pestana; Peter M. Kyne; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Rima W. Jabado (Conservation Letters)
ABSTRACT The Kunming‐Montreal Global Biodiversity Framework commits nations to conserving 30% of coastal and marine areas, “especially areas of particular importance for biodiversity.” Key Biodiversity Areas (KBAs) provide a standardized approach for recognizing sites holding a significant proportion of the global population or extent of species or ecosystems. However, concerns about the relevance of this approach for broadly distributed and/or highly mobile aquatic vertebrates prompted development of parallel approaches focused on critical areas for life‐history processes, including Important Shark and Ray Areas (ISRAs). We examine these approaches and assess whether important areas for sharks, rays, and chimaeras (“sharks”) can qualify as KBAs, by applying the KBA criteria to ISRAs. One fifth of ISRAs could be recognized as KBAs. KBAs could be recognized for three quarters of globally threatened and two thirds of non‐threatened restricted‐range sharks based on published range maps. For broadly distributed species, additional information (e.g., on aggregations) is needed to recognize important sites as KBAs. Our results show that these approaches are complementary, highlighting the potential for ISRAs to contribute to KBA assessments while ensuring important sites for sharks are mapped and available to inform government actions to meet global commitments for conserving biodiversity in coastal and marine areas.